Effect Of Design For Modularity Maintainability-A Premilary Study. - Abdullah, Ahmad Baharuddin; Hasim, M.H; Mohd Ripin, Zaidi; Shuib, S (2005)
This paper discussed the relationship between design for modularity and maintenance in order to extend product life.